The impacts of tobacco and nicotine on HIV-1 infection, inflammation, and the blood-brain barrier in the central nervous system - Keane, Aislinn M.; Swartz, Talia H. (Frontiers in Pharmacology, 2024)
Human immunodeficiency virus (HIV-1) remains a persistent global health crisis. Even while successfully virologically suppressed, people with HIV (PWH) experience a higher risk for inflammatory disorders such as HIV-associated neurocognitive disorder (HAND). Tobacco use puts PWH at higher risk for neurocognitive symptoms resulting from HIV-associated neuroinflammation. The NLR Family Pyrin Domain Containing 3 (NLRP3) inflammasome has been implicated as a driver of HIV-associated inflammation, including HAND. Nicotine, the psychoactive component of tobacco smoke, has also been shown to signal through the NLRP3 inflammasome and modulate inflammatory signaling in the CNS. Here, we explore the impacts of nicotine and tobacco on the complex neurobiology of HAND, including effects on cognition, inflammation, viral latency, and blood-brain barrier integrity. We outline nicotine’s role in the establishment of active and latent infection in the brain and posit the NLRP3 inflammasome as a common pathway by which HIV-1 and nicotine promote neuroinflammation in PWH.